Soccer players` perceptions on injury risk and prevention strategies - Hamdan, M.; Sharir, R.; Yeo, W. K.; Firhad, R. M.; Azidin, R. (Journal of Physical Education and Sport, 2022)
In injury prevention practice, high emphasis has been directed to the implementation and maintenance of evidence-based injury prevention measures into training routines. Despite scientific backing, compliance to injury prevention exercise programs has been observed to be suboptimal in many teams. Thus, understanding the soccer players` beliefs, knowledge, attitude, and behaviors toward injury prevention exercise programs may unlock some insight toward better player education and compliance of injury prevention approaches implemented in their teams. In this study, we aim to gather preliminary data on Malaysian elite soccer players` perceptions on injury risk and mechanisms, its means of prevention, and their current practice in prevention of injuries during training and matches. Active players from four elite soccer and amateur leagues (Super League, Premier League, President`s Cup, and Youth Cup) in Malaysia were invited to participate. Forty-five (n = 45) male elite players returned their responses. The most perceived risk factors for injury are muscle impairments and fatigue (91.1%), followed by coordination (88.9%), physical condition (84.4%), and previous injury (77.8%). As per our findings, over 50% of respondents feel adequately informed about injury prevention. However, as a practice, players seem to employ a combination of injury prevention measures that may or may not be supported by comprehensive, evidence-based literature. The findings suggest that there may be conflicting information among the players with regard to the efficacy of one injury prevention practice in comparison to the other. This may be regarded as a call for injury risk and prevention education among players, as well as increase the promotion of evidence-based injury prevention programs in Malaysian professional soccer.